Postponements and Cancellations of Mass Events in Ancient Rome: CIL IV 9967 in a Broader Context of Gladiatorial Games - Miączewska, Anna (Gerión. Revista de Historia Antigua, 2024)
The article examines the literary and epigraphic evidence from the ancient Roman Italy for the postponement and cancellation of various arena shows, the reasons provided, and how changes were communicated to spectators. Like mass events today, the dates of theatre and arena performances in antiquity were subject to sudden alterations, and the audience, often travelling from distant places in large numbers, somehow had to be notified of the cancellation. To offer a broader understanding of the reasons for the postponement or cancellation of games, this article also examines instances of spectator displeasure with events they attended, those they avoided altogether, and those that were cancelled. This is done with particular reference to dipinto CIL IV 9976 from Pompeii, which, it will be argued, is the only known epigraphic evidence from Roman Italy for an arena event cancellation.